A 2-year review of the general internal medicine admissions to the British Role 3 Hospital in Camp Bastion, Afghanistan. Issue 1 (3rd June 2015) - Cox, Andrew T; Lentaigne, J; White, S; Burns, D S; Parsons, I; O'Shea, M; Stacey, M; Sharma, S; Wilson, D
Abstract : Background: Detailed knowledge of the likely volume and nature of the diseases presenting to deployed secondary care facilities aids operational planning. Now the British operation in Afghanistan has ended and a record of the experience is useful to preserve the lessons learned. Methods: Over a 2-year period from April 2011, prospective demographic and clinical data were collected on consecutive general internal medicine admissions to the Role 3 Hospital in Camp Bastion, Afghanistan. Up to four different symptoms and diagnoses were coded using the WHO International Classification of Disease, V.10 for each patient. Results: A total of 1368 medical patients were admitted. Of 1131 military admissions, 612 were from the UK (54.1%) and the remainder from 13 allied countries; 237 civilians came from 23 countries. Civilians were older than the military patients (p<0.001) but included five children. The 20 most frequent presenting symptoms were identified and there were 1626 diagnoses made. The 10 most frequent diagnoses were infectious gastroenteritis (12.6%), heat illness (4.3%), pneumonia (3.6%), epilepsy (2.6%), cellulitis (2.7%), migraine (1.8%), peptic ulcer disease (1.2%), myocardial infarction (1.2%), venous thromboembolism (1.2%) and pericarditis (0.7%). In 252 cases (18.4%) a firm diagnosis was not reached and a symptom was recorded. The five most frequent of these were undifferentiated febrile illnesses (4.6%), syncope (3.7%), chest pain (2.8%), headache (0.8%) and palpitations (0.7%). The mean hospital length of stay was 1.59 days and 72.2% of UK military patients were 'returned to unit'. Three civilian patients died in hospital or following aeromedical evacuation and there were no deaths of any military patients. Discussion: This study demonstrates the wide variety of presentations seen by physicians at an established military field hospital. This information informs the core syllabus of military physician training and will help facilitate planning for future medical support to similar military operations. Trial registration number: RCDM/Res/Audit/1036/ 12/0305.